ANALISIS KONTRIBUSI PAJAK HOTEL DAN PAJAK RESTORAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) - Septahadi, Gelar (Universitas Muhammadiyah Tangerang, 2021)
Hotel and restaurant tax contributions analysis in increasing local income (PAD) Sukabumi City.This study aim,s to see and Hotel and restaurant tax contributions analysis in increasing local income (PAD) in Sukabumi City. The method use is a qualitative method with a descriptive approach. Data collection techniques used were interviews,, documentation and literature. The data analysis technique used are: 1) Data Collection, 2) Data Reduction, 3) Data Presentation, 4) Drawing Conclution and Verification.The result of this suggest that hotel and restaurant tax revenues in the last 5 years have increased to 2019, with a significant decline in 2020. As for hotel and restaurant tax contributions to the county tax revenue, the years 2020 decline. This is because of the Covid-19 pandemic and the enforcement of governmental controls (PPKM). Because it eventually saw the government of sukabumi innovation in public services that made reporting and paying taxes easier and by regularly counseling taxes to taxpayers to raise tax awareness levels in paying taxes